Análise postural e eletromiográfica e a prevalência do bruxismo em indivíduos com diferentes classes oclusais de angle - Gadotti, Inaê Caroline (Universidade Federal de São Carlos, 2003)
The parafunctions habits can be associated with malocclusion, and reflect on the posture system because of their anatomical and functional relationship, causing muscle disorders. The proposal of this study was to analyze in individuals with and without bruxism, the malocclusions prevalence (Angle classification), as well as evaluate the cervical postural behavior (head and neck) and bilateral electromyographic behavior of the anterior portion of temporal and masseter muscles. Were selected 34 female volunteers, between 17 and 27 years, and separated in two groups (with and without habits of squeeze and/or to screak the teeth). An evaluation of the occlusion was accomplished, and then a postural evaluation through a clinical analysis and through the Alcimage software, besides the electromyographic analysis, being used active differential surface electrodes. In the electromyography analysis everybody accomplished bilateral isotonic mastication with Parafilm material. According to the results, the strongest relationship evidence among head posture, malocclusions and muscle alterations, was noted on individuals with Angle class II, which presented larger electromyographic activity, larger angle in the photometric analysis and larger incidence of head anteriorization, besides all theses presented parafunction. Therefore, the association between physiotherapists and dentists is important for the treatment of patient with posture alterations and muscle dysfunction due to bruxism and malocclusion, mainly for the individuals with class II.
Keywords: Eletromiografia; Postura; Bruxismo; Oclusão; Angle; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL